IbM Kelompok Usaha Pengrajin Batik di Desa Klampar Kabupaten Pamekasan Madura - Titiek Rachmawati; Hery Murnawan; Istiono . (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract.Â Batik is one of the efforts made by the home-based business and are included Kelompok Usaha Kecil Menengah (UKM). This business unit is expected to sustain the growth of the macro economy. In operation, batik does not escape the problem to be solved. Problems faced by batik artisans di Desa Klampar Kecamatan Proppo Kabupaten Pamekasan Madura is a production technology that is used in the dyeing process is still traditional, and is unable to work with the level of quality and optimal completion time.Through Program Ipteks bagi Masyarakat (IBM), are given assistance atomizer Color (com-pressors and handspray) so expect the problem of enhancing the quality of batik and batik production can be resolved.Â Keywords: alat penyemprot warna, handspray, compressor